Do Dividend Changes have Informational Content to Signal the Market ? Evidence from the Indian Stock Market - Pandey, Vijay Shankar (Indian Journal of Research in Capital Markets, 2017)
This paper analyzed the signalling effect of stand-alone dividend decisions on the market prices of listed companies in the emerging Indian economy ; 158 events pertaining to 103 companies common to Bombay Stock Exchange (BSE) and National Stock Exchange of India Ltd. (NSE) were selected. GARCH (p q) model for the calculation of abnormal returns during the event window of 61 days for the period of 10 years was applied. The findings are indicative of the absence of signalling effect amidst inefficiency of the market for all levels of changes in stand-alone dividend announcements.